Cost-benefits analysis of social interactions: Familiarity modulates the estimation of individual contributions to joint action - Speranza, Trinidad Belen (2025)
Every day, we engage in activities that require collaboration and assistance from others. Social interactions with children are distinct because they frequently result in partners contributing different amounts of effort. This study investigates whether children and adults estimate they will have to invest different amounts of effort when engaging in joint tasks compared to doing the same task by themselves. Specifically, if this engagement is with a familiar co-actor. In 4 Experiments, children and adults estimated the weight of objects when they anticipated that they would be lifted alone and when they thought they would have help. Children and adults estimated the weight of three clear baskets carrying different weights (light, medium, and heavy). The estimated weight of objects varied for adults and children depending on whether they thought they would lift alone or together. Children reliably perceived objects as lighter when they expected help from their parents compared to lifting them alone or with the help from adults. Parents, in turn, estimated objects would be heavier when they were helping their child. Overall, results suggest that we analyze the costs and benefits of helping another person and the social bond we have with them before engaging in joint actions.